Isolation precautions cause minor delays in diagnostics and treatment of non-COVID patients - J. Paajanen; L.K. Mäkinen; A. Suikkila; M. Rehell; M. Javanainen; A. Lindahl; E. Kekäläinen; S. Kurkela; K. Halmesmäki; V.-J. Anttila; S. Lamminmäki (Elsevier, 2021)
Summary: Background: Isolation precautions are essential prevent spread of COVID-19 infection but may have a negative impact on inpatient care. The impact of these measures on non-COVID-19 patients remains largely unexplored. Aim: This study aimed to investigate diagnostic and treatment delays related to isolation precautions, the associated patient outcome, and the predisposing risk factors for delays. Methods: This observational study was conducted in seven Helsinki region hospitals during the first wave of the COVID-19 pandemic in Finland. The study used data on all non-COVID-19 inpatients, who were initially isolated due to suspected COVID-19, to estimate whether isolation precautions resulted in diagnostic or treatment delays. Results: Out of 683 non-COVID-19 patients, 33 (4.8%) had delays related to isolation precautions. Clinical condition deteriorated non-fatally in seven (1.0%) patients. The following events were associated with an increased risk of treatment or a diagnostic delay: more than three ward transfers (P = 0.025); referral to an incorrect speciality in the emergency department (P = 0.004); more than three SARS-CoV-2 RT-PCR tests performed (P = 0.022); and where cancer was the final diagnosis (P = 0.018). In contrast, lower respiratory tract symptoms (P = 0.013) decreased the risk. Conclusions: The use of isolation precautions for patients who did not have COVID-19 had minor negative effects on patient outcomes. The present study underlines the importance of targeting diagnostic efforts to patients with unspecified symptoms and to those with a negative SARS-CoV-2 test result. Thorough investigations to achieve an accurate diagnosis improves the prognosis of patients and facilitates appropriate targeting of hospital resources.